Neutrons attenuation on composite metal foams and hybrid open-cell Al foam. (April 2015) - Chen, Shuo; Bourham, Mohamed; Rabiei, Afsaneh
Abstract: A comprehensive investigation of monochromatic neutron attenuation effectiveness for close-cell composite metal foams (CMFs) and open-cell Al foam infiltrated with variety of second phase materials is presented using both experimental and theoretical methods. The experimental results indicated higher neutron flux reduction in open-cell Al foam with fillers compared to the close-cell CMFs due to their large percentage of low Z elements such as hydrogen, boron and carbon, with superior neutron attenuation performance, in their filler materials. The main factor controlling the shielding effectiveness of steel–steel CMFs is found to be the ratio of the thickness of the sphere wall to the sphere radius while the intermetallic phases in the matrix of Al–steel CMFs seem to have a major role on their shielding properties. Successful models that link the observed material properties and microstructure have been developed using Monte Carlo N -Particle Transport Code (MCNP) to verify the accuracy of the experimental results. Close-cell CMFs were proposed through three different sphere arrangements: simple cubic, body center cubic and face center cubic, whereas open-cell Al foam with fillers was represented by creating a three-dimensional structure using periodic unit cell through two approaches. The simulation results were found to be in good agreement with the experimental values. This research indicates the potential of utilizing light-weight close-cell CMFs and open-cell Al foam with fillers as nuclear shields replacing conventional materials to achieve a specified shielding level with additional benefits of excellent energy absorption and thermal isolation. Highlights: Close-cell metal foams were processed with various sphere sizes. Open-cell foams were infiltrated with hydrogen-rich fillers. Open-cell foams with fillers exhibit excellent neutron shielding efficiency. Close-cell CMFs were modeled through simple, body center, and face center cubic structures. Open-cell foams were modeled using periodic unit cell through two approaches.